Control of a super-capacitor energy storage system to mimic inertia and transient response improvement of a direct current micro-grid. (December 2020) - Jami, Mehran; Shafiee, Qobad; Gholami, Mehrdad; Bevrani, Hassan
Highlights: A virtual inertia control strategy is proposed to achieve an increased inertia from an energy storage system based on supercapacitor (SC) in the context of dc MG applications. Virtual inertia loop is implemented in inner current control loop. It proposes a derivative term which is fast enough to decrease rate of change of dc bus voltage (RoCoV) by using virtual capacitance. This emulates the virtual inertia concept. The proposed proportional term in the virtual inertia loop increases damping of dc bus voltage by using virtual conductance that emulates damping coefficient concept. The SC's voltage is regulated by a PI compensator which is implemented in outer voltage loop. The small-signal stability is considered to study the system behavior under small disturbances or load perturbations at some steady-state operational points. The analysis is validated by using the eigenvalue analysis and time-domain simulation. Abstract: In dc microgrids (dc MGs), the dc link capacitor is very small to provide the inherent inertial. As a result, large voltage deviations occur during load changes or uncertain fluctuations from the fluctuated power resources. This leads to degradation of voltage quality. To overcome the low inertia problem, this paper proposes a fast-responding energy storage system such as supercapacitor can mimic inertial responses through some specified control algorithm. A bidirectional dc–dc converter is used for interfacing supercapacitor energy storage to a dc MG. The proposed control scheme is composed of a virtual capacitor and a virtual conductance. It is implemented in the inner loop controls, i.e. current loop control to be fast enough emulating inertia and damping concept. In order to study the stability of dc MG, a comprehensive small-signal model is derived and then, an acceptable range of inertia response parameters is determined by using the system's root locus analysis. Performance of the proposed control structure is demonstrated through numerical simulations.